Multicarrier-SPWM Based Novel 7-Level Inverter Topology with Photovoltaic System - R. Palanisamy; V. Sinmayee; K. Selvakumar; K. Vijayakumar (Institute of Advanced Engineering and Science, 2017)
In this paper a novel 5 switch seven level DC-AC inverter is being proposed. The proposed multilevel inverter uses reduced number of switches as compared to the switches used in the conventional multilevel inverter. The inverter has been designed to generate a 7 level AC output using 5 switches. The voltage stress on each of the switches as well as the switching losses is found to be less, minimized common mode voltage (CMV) level and reduced total harmonic distortion. The proposed 7-level inverter topology has four dc sources, which is energized through the PV system. Proposed inverter is controlled with help of multicarrier sinusoidal pulse width modulation (MCSPWM).The simulation and hardware results were verified using matlab simulink and dspic microcontroller respectively.